Commodity-based Sovereign Wealth Funds : Managing Financial Flows in the Context of the Sovereign Balance Sheet - Al-Hassan, Abdullah (IMF Working Papers; Working Paper ;, 2018)
Commodity-based sovereign wealth funds (SWFs) have been at a crossroads following the recent fall in commodity prices. This paper provides a framework for commodity-based SWF management, focusing on stabilization and savings funds, by (i) examining macrofiscal linkages for SWFs; (ii) presenting an integrated sovereign asset and liability management (SALM) approach to SWF management; and (iii) applying this framework to a scenario where assets are being accumulated and to a scenario where the SWF is drawn on to cover a financing gap due to lower commodity prices.